Structural Cointegration of Exchange Rate, Gross Domestic Product, and External Debt in Indonesia: An Analysis of Macroeconomic Stability with the ARDL–ECM Approach - Suripto, Suripto; Athfal , Azkal Azkiya; Kurniawan, Mahrus Lutfi Adi; Salim, Agus (Universitas Muhammadiyah Ponorogo, 2025)
This study examines the relationship between Indonesia's external Debt (ULN), gross domestic product (GDP), and exchange rate (ER) using quarterly data from 2011Q1 to 2025Q2. The Autoregressive Distributed Lag (ARDL) method tests long-run cointegration, followed by an Error Correction Model (ECM) to capture short-run dynamics. The selected ARDL (1, 0, 2) model confirms a long-term relationship among external Debt, GDP, and the exchange rate. In the short run, the exchange rate has a significant impact, while GDP does not. The negative and considerable error correction term (ECT) indicates the presence of an adjustment mechanism toward equilibrium. Impulse response analysis reveals that external debt responds strongly to exchange rate shocks, and variance decomposition identifies exchange rate fluctuations as the primary contributor to debt variation. Policy recommendations include diversifying foreign debt portfolios, strengthening foreign exchange reserves, and enhancing fiscal–monetary coordination to mitigate exchange rate risks and improve long-term debt management.